The relationship between El Niño Southern Oscillation (ENSO) and oceanographic parameters in North Sulawesi waters - Lasut, Astrid Y.; Patty, Wilhelmina; Warouw, Veibe; Sondakh, Calvyn A.; Bara, Robert A.; Luasunaung, Alfret; Sumilat, Deiske A. (AQUATIC SCIENCE & MANAGEMENT, 2021)
Information about oceanographic conditions is important to determine the fertility level of waters. Oceanographic parameters in water can be influenced by global climate factors, one of them is the ENSO (El Niño Southern Oscillation) phenomenon. There have been many studies on the effect of ENSO phenomenon on oceanographic variability, but no studies have been carried out in the waters of North Sulawesi. This study aims to determine the effect of the ENSO phenomenon on the variability distribution of oceanographic parameters in North Sulawesi waters. The data used for this study were Sea Surface Temperature (SST) and chlorophyll-a from the AQUA-MODIS imaging results, wind reanalysis results from ECMWF, and Nino 3.4 index as an indicator of ENSO from NOAA. The data were processed and analyzed using quantitative analysis methods in the form of graphics. The results showed an indirect effect of the ENSO phenomenon on SST parameters and chlorophyll-a. This is because the effect of the ENSO phenomenon occurred in a certain period:  when strong El Niño triggered low temperatures of sea surface and high chlorophyll-a, and when La Niña was strong it triggered high temperatures of sea surface and low chlorophyll-a. Meanwhile, the wind speed pattern showed an insignificant effect because the wind speed was still dominated by the influence of the monsoon pattern.Indonesian title: Hubungan antara El Niño Southern Oscillation (ENSO) dan parameter oseanografi di perairan Sulawesi Utara